The effect of home-based telehealth and postpartum care given according to watson's theory of human caring on the improvement in the emotional state of the mother during the pandemic process: a case report - YILDIZ, HATİCE (My University, 2023)
Objective: The purpose of this case report was to evaluate the effect of telehealth and postpartum care provided to a mother with maternal depression according to Watson\"s Theory of Human Caring during the pandemic on the improvement in the mother\"s emotional state and to evaluate the applicability of the model. Methods: Edinburgh Postnatal Depression Scale was administered to eight women who responded to the announcement made on social media, and verbal and written permission was obtained from the mother with the highest scale score. A total of six video calls were made with the mother via WhatsApp, twice a week in the first week after postnatal discharge and once a week in the next 4 weeks, in accordance with the form drawn up according to Watson\"s Theory of Human Caring. Results: In this study, it was observed that home-based telehealth and postpartum care provided using Watson\"s Theory of Human Caring, which includes a holistic approach, was very useful, and the care provided according to the model provided a positive improvement in the emotional state of the mother with depression. Conclusions: It was concluded that telehealth and postpartum care is useful in home-based care in extraordinary situations/quarantine conditions such as pandemic; care can also be provided in the form of telehealth service according to Watson\"s Theory of Human Caring to mothers with depression; and care provides positive improvement in the emotional state of mothers.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Medicine; Internal Medicine Sciences; Family Medicine; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Klinik Tıp (MED); Klinik Tıp; TIBBİ BİLİŞİM; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICAL INFORMATICS; HEALTH CARE SCIENCES & SERVICES; Tıbbi Bilişim; Sağlık Bilgi Yönetimi; Health Informatics; Health Information Management; emotional well-being; pandemic; postpartum care; telecare; telehealth; telemedicine; Watson's Theory of Human Caring